Selective oxidation of methane by the bis(mu-oxo)dicopper core stabilized on ZSM-5 and mordenite zeolites - Groothaert, Marijke H; Smeets, Pieter J; Sels, Bert F; Jacobs, Pierre A; Schoonheydt, Robert A (Journal of the American Chemical Society, 2005)
This work reports on the capability of the O2-activated Cu-ZSM-5 and Cu-MOR zeolites to selectively convert methane into methanol at a temperature of 398 K. A strong correlation between (i) the activity and (ii) the intensity of the 22 700 cm-1 UV-vis band, assigned to the bis(mu-oxo)dicopper core, is found (i) as a function of the reaction temperature, (ii) as a function of the Cu loading of the zeolite, and (iii) in comparison to other Cu materials. These three lines of evidence firmly support the key role of the bis(mu-oxo)dicopper core in this selective, low-temperature hydroxylation of methane.